2004
DOI: 10.21273/jashs.129.4.0467
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Blue Light Effects on the Histology of Lettuce and Soybean Leaves and Stems

Abstract: Blue light (320 to 496 nm) alters hypocotyl and stem elongation and leaf expansion in short-term, cell-level experiments, but histological effects of blue light in long-term studies of whole plants have not been described. We measured cell size and number in stems of soybean (Glycine max L.) and leaves of soybean and lettuce (Lactuca sativa L.), at two blue light fractions. Short-term studies have shown that cell expansion in stems is rapidly inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 13 publications
(23 reference statements)
6
54
2
1
Order By: Relevance
“…These results support earlier evidence that increasing the ratio of R to B light increases the hypocotyl length in lettuce [45]. The lower leaf LA and plant height in treatments with high B/R light ratios may be associated with a B light-mediated inhibition of cell expansion [46]. A similar result was reported by Samuoliene et al [47], who showed that an optimal combination of B/R light ratios enhances the plant growth rate in controlled conditions.…”
Section: Lettuce Morphology Characteristics Are Affected By the B/r Lsupporting
confidence: 91%
“…These results support earlier evidence that increasing the ratio of R to B light increases the hypocotyl length in lettuce [45]. The lower leaf LA and plant height in treatments with high B/R light ratios may be associated with a B light-mediated inhibition of cell expansion [46]. A similar result was reported by Samuoliene et al [47], who showed that an optimal combination of B/R light ratios enhances the plant growth rate in controlled conditions.…”
Section: Lettuce Morphology Characteristics Are Affected By the B/r Lsupporting
confidence: 91%
“…However, these responses to higher blue light do not correspond with the literature, which reports a blue light-induced reduction in lettuce leaf area and SLA [5,9]. Smaller, thicker leaves under higher blue light have been associated with a decrease in the size and number of leaf epidermal cells, which tend to reduce overall plant growth due to a reduction in radiation capture [3]. Although we did find a general growth (shoot dry mass) reduction in response to blue light, it cannot be attributed to a decrease in light interception from smaller, thicker leaver ( Figure 2D).…”
Section: Growth Parameterscontrasting
confidence: 65%
“…Increasing blue light (400 nm to 500 nm) often inhibits cell division and expansion, reducing leaf area and stem elongation, and increasing leaf thickness in most plant species; compact plants with smaller, thicker leaves typically result in higher photosynthetic rate per unit of leaf area, but reduced radiation capture [3]. This reduction in radiation capture is believed to be the primary reason for reduced growth (dry mass gain) in response to higher blue light [4].…”
Section: Introductionmentioning
confidence: 99%
“…First, green light can penetrate deeper into the plant canopy and, therefore, drive more photosynthesis. Second, reducing the amount of blue reduces the restriction on leaf expansion imposed by plant photoreceptors (Dougher and Bugbee ), thus increasing leaf area, light capture and growth. Research to date suggests that addition of green light to the growth spectrum does not enhance crop performance in all cases.…”
Section: The Influence Of Light Quality On Plant Growthmentioning
confidence: 99%